2012
DOI: 10.1111/j.1467-8683.2011.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

CEO Power and Risk Taking: Evidence from the Subprime Lending Industry

Abstract: Manuscript Type: EmpiricalResearch Question/Issue: There is a general consensus that the lack of restraint by US financial firm executives to engage in risky subprime mortgage lending practices played a contributing role in both the inflation and deflation of the housing bubble at the heart of the global financial crisis. Evidence is less clear on what influenced the managerial proclivity to ignore warning signs and take on more and more risk to the detriment of numerous firm stakeholders. Our study examines t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
150
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(196 citation statements)
references
References 170 publications
(263 reference statements)
18
150
0
2
Order By: Relevance
“…The proportion of the non-executive directors is also negatively significant correlated with both insolvency risk and liquidity risk, which is consistent with studies of [23,26,43]. CEO's duality is found positive significantly with only credit risk, which is consistent with the studies suggesting that CEO duality increases the CEO power and give him motivates to take more risks [31,39,44]. Board female is positively significant related to Z-score indicating that more board female reduces bank insolvency risk.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The proportion of the non-executive directors is also negatively significant correlated with both insolvency risk and liquidity risk, which is consistent with studies of [23,26,43]. CEO's duality is found positive significantly with only credit risk, which is consistent with the studies suggesting that CEO duality increases the CEO power and give him motivates to take more risks [31,39,44]. Board female is positively significant related to Z-score indicating that more board female reduces bank insolvency risk.…”
Section: Resultssupporting
confidence: 81%
“…This result indicates that when the CEO is the chairman this increase the CEO power and give him motivates to take more risks These findings are consistent with [31,39,44].…”
Section: Results Of Correlation and Regression Analysissupporting
confidence: 81%
“…Studies have shown that greater CEO power induces risk taking, e.g., engaging in risky subprime mortgage lending (Lewellyn & Muller-Kahle, 2012) or strategic deviance from general tendencies (Tang, Crossan, & Rowe, 2011). Relatedly, the predecessor CEO remaining as the board chair hinders strategic change (Quigley & Hambrick, 2012).…”
Section: Upper Echelons Theorymentioning
confidence: 99%
“…Executive tenure is one of the most studied attributes of executives in the risk-taking literature-long-tenured executives are reluctant to make changes and thus take fewer risks (Boeker, 1997a;Hambrick & Fukutomi, 1991;Hambrick, Geletkanycz, & Fredrickson, 1993;Miller, 1991). New executives, however, are more likely to support new product-market entry (Boeker, 1997b), experimentation (Miller & Shamsie, 2001), technological dynamism (Wu, Levitas, & Priem, 2005), innovation (Chaganti & Sambharya, 1987;Thomas, Litschert, & Ramaswamy, 1991), R&D spending (Barker & Mueller, 2002), and risky subprime mortgage lending (Lewellyn & Muller-Kahle, 2012).…”
Section: Upper Echelons Theorymentioning
confidence: 99%
“…Social psychology also suggests that an elevated power may increase (decrease) an individual's sensitivity to rewards (threat) (Keltner et al, 2003). This approach-related behavior often results in risk-taking (Lewellyn & Muller-Kahle, 2012). Therefore, the relationship between managerial power and risk-taking is ambiguous.…”
Section: ⅱ Hypothesis Developmentmentioning
confidence: 99%